American diversity : a demographic challenge for the twenty-first century - Denton, Nancy A.; Tolnay, Stewart Emory (State University of New York Press, 2002)
"Presenting important work by well-known demographers, American Diversity focuses on U.S. population changes in the twenty-first century, emphasizing the nation's increasing racial and ethnic diversity. Rather than focusing on separate groups sequentially, this work emphasizes comparisons across groups and highlights how demographic and social structural processes affect all groups. Specific topics covered include the formation of race and ethnicity; population projections by race; immigration, fertility, and morality differentials; segregation; work and education; intermarriage; aging; and racism."--Jacket